THE INFLUENCE OF WORKERS AND WORK COMMITMENTS OF WOODEN HOUSE CRAFTSMEN ON WOOD WASTE MANAGEMENT BEHAVIOR IN THE WOODEN INDUSTRY TANJUNG BATU SEBERANG VILLAGE TANJUNG BATU DISTRICT – OGAN ILIR REGENCY - Zarkasih, Muhammad Restu; Susanti, Retno; Azwardi, Azwardi (Jurnal Pendidikan Geografi Gea, 2020)
The purpose of this study was to examine the influence of workers and work commitments of wooden house craftsmen on wood waste management behavior in the wooden industry Tanjung Batu Seberang Village Tanjung Batu District – Ogan Ilir Regency which is the village that produces the biggest wooden houses in South Sumatra Province. The population of this study was 142 people with a sample of 59 respondents which is determined by the Taro Yamane formula. Data were collected using a questionnaire using a Likert measurement scale. The method used in this research is correlation descriptive method, sedangkan teknik analisis data yang digunakan adalah analisis regresi linear berganda. while the data analysis technique used is multiple linear regression analysis. The feasibility of the research instrument is measured by the validity test and the reliability test. While for the classic assumption test using the normality test, multicollinearity test, heterokedasticity test, and the coefficient of determination test (R2). Hypothesis testing uses the simultaneous test (Test F). The results showed that the workers and work commitments of wooden house craftsmen simultaneously affect on wood waste management behavior in the wooden industry. The author recommends that the government of Ogan Ilir Regency to encourage and socialize awareness of the environment. wooden house craftsmen expected to pay more attention in wood waste management and began to think about how to treat wood waste become a useful new item, thus minimizing waste discharged into the environment.